2022
DOI: 10.36401/jipo-22-10
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-7 in the Formation of Tertiary Lymphoid Structures and Their Prognostic Value in Gastrointestinal Cancers

Abstract: Immunotherapies for the treatment of solid tumors continue to develop in preclinical and clinical research settings. Unfortunately, for many patients the tumor fails to respond or becomes resistant to therapies such as checkpoint inhibitors (CPIs) targeting programmed cell death protein-1 (PD-1), programmed death-ligand 1 (PD-L1), and cytotoxic T lymphocyte antigen-4 (CTLA-4). In many cancers, failed response to CPIs can be attributed to poor T cell infiltration, dominant immunosuppression, and exhausted immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 102 publications
(206 reference statements)
0
2
0
Order By: Relevance
“…Further studies are required to determine the specific mechanisms. TLSs have been reported to be associated with increased infiltration of B and T cells ( 32 ). We found that the TLS hub gene, TNFSF14, was enriched in a T-cell cluster based on single-cell sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to determine the specific mechanisms. TLSs have been reported to be associated with increased infiltration of B and T cells ( 32 ). We found that the TLS hub gene, TNFSF14, was enriched in a T-cell cluster based on single-cell sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of TLS depends on intricate ligand-receptor interactions between different cell types, including innate lymphocytes (ILCs), stromal cells, endothelial cells and B cells. CD3-CD4-/+ CXCR5IL-7Rα + hi ILCs, also known as lymphoid tissue inducing cells (LTi), are an essential component of SLO development [22]. Stromal fibroblasts, characterized by the expression of podoplanin and fibroblast activation protein-α (FAP), have been shown to be associated with the formation of TLS in both mouse and human models [23,24].…”
Section: Formation and Maturation Of Tlsmentioning
confidence: 99%